Survival of adults with rheumatoid arthritis associated interstitial lung disease - A systematic review and meta-analysis - Farquhar, HJ; Beckert, N; Beckert, L; Edwards, AL; Matteson, EL; Frampton, C; Stamp, LK (Seminars in arthritis and rheumatism, 2023)
Rheumatoid arthritis associated interstitial lung disease (RA-ILD) is associated with high levels of morbidity and mortality. The primary aim of this systematic review was to determine the duration of survival, from time of diagnosis of RA-ILD. Medline (Ovid), Embase (OVID), CINAHL (EBSCO), PubMed, and the Cochrane Library were searched for studies that reported duration of survival from time of diagnosis of RA-ILD. Risk of bias of included studies was assessed based upon 4 domains of the Quality In Prognosis Studies tool. Results for median survival were presented by tabulation and discussed qualitatively. Meta-analysis of cumulative mortality at 1 year, >1y to ≤3 years, >3 years to ≤5 years, and >5 years to≤ 10 years was undertaken, for total RA-ILD population, and according to ILD pattern. 78 studies were included. Median survival for the total RA-ILD population ranged from 2 to 14 years. Pooled estimates for cumulative percentage mortality up to 1 year were 9.0% (95% CI 6.1, 12.5, I2 88.9%), >1 to ≤3 years 21.4% (17.3, 25.9, I2 85.7%), >3 to ≤ 5 years 30.2% (24.8, 35.9, I2 87.7%), and > 5 to ≤ 10 years 49.1% (40.6, 57.7 I2 85.0%). Heterogeneity was high. Only 15 studies were rated as low risk of bias in all 4 domains assessed. This review summarises the high mortality of RA-ILD, however the strength of conclusions that can be made is limited by the heterogeneity of the available studies, due to methodological and clinical factors. Further studies are needed to better understand the natural history of this condition.